Práticas de leitura da biblioteca de uma escola do campo: possibilidades, limites e contradições - Queiroz, Solange Palhano de (2015)
The object of this research is analyzing the reading`s conceptions and practices occurred at a rural school`s library, situated in Guarapuava`s city, district Guará, considering the role it plays on the promotion of literary reading. It takes base on the theoretical references about language`s dialogical dimension, starting from the assumptions of Bakhtin`s Interactionist Theory (2004); passing by the emphasis on the reader taking from Aesthetic of Reception (JAUSS, 1994; ZILBERMAN, 1989); until the promotion of reading on the literary education and the library`s role on the generation of readers considering points of view from theorists like Aguiar (2006), Colomer (2003), Fragoso (2011), Perrotti (1990), and Silva (1988). The principal aim is identifying the contribution and relevance of the library to formation of rural school`s readers since related studies and proposals from Rural Education`s Curriculum Guidelines. As proceedings, it adopts firstly the analysis of official documentation that guide the school`s actions, aiming to seize the importance attributed to the library on the reader`s formation, highlighting the extent to which this space is perceived as relevant in the official documentation. At a second step it develops a qualitative research using interviews with both a Portuguese Language`s teacher and a school`s librarian. By the analyze of those statements, it pursuits: understanding of the conception of reading submitted by that subject`s teacher since the application of State Curriculum Guidelines - for both Portuguese Language and Rural Schools; identifying the conceptions developed, at the practice, and its reflections for the school library as to reader`s formation, as well as its relation with the library and the work of reading at the rural school. Thereby, it aims to compare the limitations and contradictions in the research subjects` discourse to the possibilities to the rural school`s library. As result, it infers that beside the importance of the school`s library on the reader`s formation which is showed at texts related to reading and literature teaching`s tissues, as well as at research subjects` discourses, in practice its role is still restricted to storage of books and a space of silent study of specific scholar`s points, indicating some slight to pedagogical and social potential of the library, as demonstrated by its absence in official documentation at Paraná State Curriculum Guidelines for both Portuguese Language and Rural Education. In face of that, this research also aims propitiating to the rural school`s library subsidies to promote news and varied actions toward educational activities as literary, social and cultural activities.